Cauchy's Mean Theorem/Proof 1
Theorem
Let $x_1, x_2, \ldots, x_n \in \R$ be real numbers which are all positive.
Let $A_n$ be the arithmetic mean of $x_1, x_2, \ldots, x_n$.
Let $G_n$ be the geometric mean of $x_1, x_2, \ldots, x_n$.
Then:
- $A_n \ge G_n$
with equality holding if and only if:
- $\forall i, j \in \set {1, 2, \ldots, n}: x_i = x_j$
That is, if and only if all terms are equal.
Proof
The arithmetic mean of $x_1, x_2, \ldots, x_n$ is defined as:
- $\ds A_n = \frac 1 n \paren {\sum_{k \mathop = 1}^n x_k}$
The geometric mean of $x_1, x_2, \ldots, x_n$ is defined as:
- $\ds G_n = \paren {\prod_{k \mathop = 1}^n x_k}^{1/n}$
We prove the result by induction:
For all $n \in \Z_{>0}$, let $\map P n$ be the proposition:
- For all positive real numbers $x_1, x_2, \ldots, x_n: A_n \ge G_n$.
$\map P 1$ is true, as this just says:
- $\dfrac {x_1} 1 \ge {x_1}^{1/1}$
which is trivially true.
Basis for the Induction
$\map P 2$ is the case:
- $\dfrac {x_1 + x_2} 2 \ge \sqrt {x_1 x_2}$
As $x_1, x_2 > 0$ we can take their square roots and do the following:
\(\ds 0\) | \(\le\) | \(\ds \paren {\sqrt {x_1} - \sqrt {x_2} }^2\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds x_1 - 2\sqrt {x_1 x_2} + x_2\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \sqrt {x_1 x_2}\) | \(\le\) | \(\ds \frac {x_1 + x_2} 2\) |
This is our basis for the induction.
Induction Hypothesis
Now we show that:
- $(1): \quad$ If $\map P {2^k}$ is true, where $k \ge 1$, then it logically follows that $\map P {2^{k + 1} }$ is true
- $(2): \quad$ If $\map P k$ is true, where $k \ge 2$, then it logically follows that $\map P {k - 1}$ is true.
The result will follow by Forward-Backward Induction.
This is our first induction hypothesis:
- $A_{2^k} \ge G_{2^k}$
Then we need to show:
- $A_{2^{k + 1} } \ge G_{2^{k + 1} }$
Induction Step
This is our induction step:
Let $m = 2^k$.
Then $2^{k + 1} = 2 m$.
Because $\map P m$ is true:
- $\paren {x_1 x_2 \dotsm x_m}^{1/m} \le \dfrac 1 m \paren {x_1 + x_2 + \dotsb + x_m}$
Also:
- $\paren {x_{m + 1} x_{m + 2} \dotsm x_{2 m} }^{1/m} \le \dfrac 1 m \paren {x_{m + 1} + x_{m + 2} + \dotsb + x_{2 m} }$
But we have $\map P 2$, so:
- $\paren {\paren {x_1 x_2 \dotsm x_m}^{1/m} \paren {x_{m + 1} x_{m + 2} \dotsm x_{2 m} }^{1/m} }^{1/2} \le \dfrac 1 2 \paren {\dfrac {x_1 + x_2 + \cdots + x_m} m + \dfrac {x_{m + 1} + x_{m + 2} + \dotsb + x_{2 m} } m}$
So:
- $\paren {x_1 x_2 \dotsm x_{2 m} }^{1/2m} \le \dfrac {x_1 + x_2 + \dotsb + x_{2 m} } {2 m}$
So $\map P {2 m} = \map P {2^{k + 1} }$ holds.
So $\map P {2^n}$ holds for all $n$ by induction.
Now suppose $\map P k$ holds.
Then:
\(\ds \paren {x_1 x_2 \dotsm x_{k - 1} G_{k - 1} }^{1/k}\) | \(\le\) | \(\ds \dfrac {x_1 + x_2 + \dotsm + x_{k - 1} + G_{k - 1} } k\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {G_{k - 1}^{k - 1} G_{k - 1} }^{1/k}\) | \(\le\) | \(\ds \dfrac {\paren {k - 1} A_{k - 1} + G_{k - 1} } k\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds k G_{k - 1}\) | \(\le\) | \(\ds \paren {k - 1} A_{k - 1} + G_{k - 1}\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {k - 1} G_{k - 1}\) | \(\le\) | \(\ds \paren {k - 1} A_{k - 1}\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds G_{k - 1}\) | \(\le\) | \(\ds A_{k - 1}\) |
So $\map P k \implies \map P {k - 1}$ and the result follows by Forward-Backward Induction.
Therefore $A_n \ge G_n$ for all $n$.
$\blacksquare$
Proof of Equality Condition
Necessary Condition
Let:
- $\forall i, j \in \set {1, 2, \ldots, n}: x_i = x_j = x$
Then:
\(\ds A_n\) | \(=\) | \(\ds \dfrac 1 n \sum_{j \mathop = 1}^n x\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac 1 n n x\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds x\) |
\(\ds G_n\) | \(=\) | \(\ds \paren {\prod_{j \mathop = 1}^n x}^{\frac 1 n}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \paren {x^n}^{\frac 1 n}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds x\) |
So:
- $A_n = G_n = x$
$\Box$
Sufficient Condition
Let $A_n = G_n$.
We prove the result by induction:
For all $n \in \Z_{>0}$, let $\map P n$ be the proposition:
- $A_n = G_n \implies \forall i, j \in \set {1, 2, \ldots, n}: x_i = x_j$
$\map P 1$ is true, as this just says:
\(\ds A_1\) | \(=\) | \(\ds G_1\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \dfrac 1 1 \sum_{j \mathop = 1}^1 x_j\) | \(=\) | \(\ds \paren {\prod_{j \mathop = 1}^1 x_j}^{1/1}\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds x_1\) | \(=\) | \(\ds x_1\) |
which is trivially true.
Basis for the Induction
$\map P 2$ is the case:
\(\ds A_2\) | \(=\) | \(\ds G_2\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \dfrac {x_1 + x_2} 2\) | \(=\) | \(\ds \sqrt {x_1 x_2}\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {\dfrac {x_1 + x_2} 2}^2\) | \(=\) | \(\ds x_1 x_2\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds x_1^2 + 2 x_1 x_2 + x_2^2\) | \(=\) | \(\ds 4 x_1 x_2\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds x_1^2 - 2 x_1 x_2 + x_2^2\) | \(=\) | \(\ds 0\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {x_1 - x_2}^2\) | \(=\) | \(\ds 0\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds x_1\) | \(=\) | \(\ds x_2\) |
This is our basis for the induction.
Induction Hypothesis
Now we show that:
- $(1): \quad$ If $\map P k$ is true, where $k \ge 1$, then it logically follows that $\map P {2 k}$ is true
- $(2): \quad$ If $\map P k$ is true, where $k \ge 2$, then it logically follows that $\map P {k - 1}$ is true.
The result will follow by Forward-Backward Induction.
This is our first induction hypothesis:
- $A_k = G_k \implies \forall i, j \in \set {1, 2, \ldots, k}: x_i = x_j = x$
Also, let:
- $A_k' := \ds \dfrac 1 k \sum_{j \mathop = k + 1}^{2 k} x_j = y$
and:
- $G_k' := \ds \paren {\prod_{j \mathop = k + 1}^{2 k} }^{1 / k} x_j = y$
By the induction hypothesis:
- $A_k' = G_k' \implies \forall i, j \in \set {k + 1, k + 2, \ldots, 2 k}: x_i = x_j = y$
We need to show:
- $A_{2 k} = G_{2 k} \implies \forall i, j \in \set {1, 2, \ldots, 2 k}: x_i = x_j = x$
Induction Step
This is our induction step:
Suppose:
- $A_{2 k} = G_{2 k}$
Let:
- $A_k' := \ds \dfrac 1 k \sum_{j \mathop = k + 1}^{2 k} x_j = y$
and:
- $G_k' := \ds \paren {\prod_{j \mathop = k + 1}^{2 k} }^{1 / k} x_j = y$
By the induction hypothesis:
- $A_k' = G_k' \implies \forall i, j \in \set {k + 1, k + 2, \ldots, 2 k}: x_i = x_j = y$
Then:
\(\ds A_{2 k}\) | \(=\) | \(\ds \dfrac 1 {2 k} \sum_{j \mathop = 1}^{2 k} x_j\) | Definition of Arithmetic Mean | |||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac 1 {2 k} \paren {\sum_{j \mathop = 1}^k x_j + \sum_{j \mathop = k + 1}^{2 k} x_j}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac 1 2 \paren {\dfrac 1 k \sum_{j \mathop = 1}^k x_j + \dfrac 1 k \sum_{j \mathop = k + 1}^{2 k} x_j}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac 1 2 \paren {A_k + A_k'}\) | Definition of Arithmetic Mean | |||||||||||
\(\ds \) | \(=\) | \(\ds \dfrac 1 2 \paren {x + y}\) | Definition of $A_k$ and $A_k'$ |
\(\ds G_{2 k}\) | \(=\) | \(\ds \paren {\prod_{j \mathop = 1}^{2 k} x_j}^{1 / 2 k}\) | Definition of Geometric Mean | |||||||||||
\(\ds \) | \(=\) | \(\ds \paren {\paren {\prod_{j \mathop = 1}^{2 k} x_j}^{1 / k} }^{1 / 2}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \paren {\paren {\prod_{j \mathop = 1}^k x_j}^{1 / k} \times \paren {\prod_{j \mathop = k + 1}^{2 k} x_j}^{1 / k} }^{1 / 2}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \paren {G_k G_k'}^{1 / 2}\) | Definition of Geometric Mean | |||||||||||
\(\ds \) | \(=\) | \(\ds \paren {x y}^{1 / 2}\) | Definition of $G_k$ and $G_k'$ |
Then:
\(\ds A_{2 k}\) | \(=\) | \(\ds G_{2 k}\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \dfrac 1 2 \paren {x + y}\) | \(=\) | \(\ds \paren {x y}^{1 / 2}\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds x\) | \(=\) | \(\ds y\) | Basis for the Induction |
That is:
- $\forall i, j \in \set {1, 2, \ldots, k}: x_i = x_j = x$
- $\forall i, j \in \set {k + 1, k + 2, \ldots, 2 k}: x_i = x_j = x$
Hence:
- $\forall i, j \in \set {1, 2, \ldots, 2 k}: x_i = x_j = x$
Now suppose $\map P k$ holds.
Then:
\(\ds G_{k - 1}\) | \(=\) | \(\ds A_{k - 1}\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {k - 1} G_{k - 1}\) | \(=\) | \(\ds \paren {k - 1} A_{k - 1}\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds k G_{k - 1}\) | \(=\) | \(\ds \paren {k - 1} A_{k - 1} + G_{k - 1}\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {G_{k - 1}^{k - 1} G_{k - 1} }^{1/k}\) | \(=\) | \(\ds \dfrac {\paren {k - 1} A_{k - 1} + G_{k - 1} } k\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {x_1 x_2 \dotsm x_{k - 1} G_{k - 1} }^{1 / k}\) | \(=\) | \(\ds \dfrac {x_1 + x_2 + \dotsm + x_{k - 1} + G_{k - 1} } k\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \paren {x_1 x_2 \dotsm x_{k - 1} G_{k - 1} }^{1 / k}\) | \(=\) | \(\ds \dfrac {x_1 + x_2 + \dotsm + x_{k - 1} + G_{k - 1} } k\) |
But:
- $\paren {x_1 x_2 \dotsm x_{k - 1} G_{k - 1} }^{1 / k}$ is the geometric mean of $\set {x_1, x_2, \ldots, x_{k - 1}, G_{k - 1} }$
- $\dfrac {x_1 + x_2 + \dotsm + x_{k - 1} + G_{k - 1} } k$ is the arithmetic mean of $\set {x_1, x_2, \ldots, x_{k - 1}, G_{k - 1} }$
We have that $\set {x_1, x_2, \ldots, x_{k - 1}, G_{k - 1} }$ has $k$ elements.
Hence by the induction hypothesis:
- $\forall i, j \in \set {1, 2, \ldots, k - 1}: x_i = x_j = G_{k - 1}$
So $\map P k \implies \map P {k - 1}$ and the result follows by Forward-Backward Induction.
Therefore $A_n \ge G_n$ for all $n$.
- $\forall n \in \N: A_n = G_n \implies \forall i, j \in \set {1, 2, \ldots, n}: x_i = x_j$
$\blacksquare$
Sources
- 1977: K.G. Binmore: Mathematical Analysis: A Straightforward Approach ... (previous) ... (next): $\S 3$: Natural Numbers: $\S 3.10$: Example